Climate change and environment issues in cyber media construction in Indonesia - Muslikhin, Muslikhin; Prawira, Indra (Universitas Padjadjaran, 2023)
Background: The issue of climate change and the environment has not become the primary focus of the media in Indonesia, but it is frequently featured in the news. This occurs because the media fulfils its function as a provider of information. Purpose: This study seeks to explain how cyber media constructs climate change and environmental issues in the news. Methods: Research with a qualitative approach and qualitative descriptive methods, with critical discourse analysis as the data analysis technique. The websites Kompas.com, Okezone.com, and Suara.com are the subject of study. Results: According to the study, climate is the word that appears the most frequently in the text of the three media. Change is the term that appears most frequently on Kompas.com and Suara.com. Indonesia is the most popular search term on Okezone.com. At the level of production, cyber media lacks an agenda-setting team, a dedicated channel, or a specialized team devoted to the environment and climate change. At the social level, they only generate news related to the environment and climate change if it has gone viral and is trending on social media. Conclusion: The research concludes that there are both distinctions and similarities among the three cyber media in terms of the words that appear most frequently in news articles about environmental issues and climate change. They lack agenda-setting, a dedicated channel, and a specialized team. They are oblivious to environmental issues and climate change. Implications: The research has implications for agenda setting from theoretical implications. The media does not set an agenda and only follows the viral, trending, and important public issues. The implication is that cyber media gives viral issues a news value.